Halal Training Practices Among Food Handlers In Sibu, Sarawak: A Qualitative Study At YS Cakery Dan dalam f - Mohamad Jefri, Nur Afina Syahida; Shahrom, Nur Fatin Nabilah; Mohd Talib, Nurliyana (Journal of Islamic, Social, Economics and Development, 2025)
Halal food preparation and handling are important parts of the food service industry in Malaysia where most population are Muslims. This study explores the effectiveness of halal training among certified food handlers in Sibu, Sarawak. As a multicultural town with growing food businesses, Sibu faces challenges in ensuring halal compliance, particularly in premises managed by non-Muslims or those unfamiliar with halal principles. The main objective of this research is to evaluate the level of knowledge, attitude, and practice among food handlers after attending halal training and to identify challenges they face. This research used a qualitative approach through semi-structured interviews with four informants holding various roles in YS bakery setting. The findings show that halal training significantly improves awareness, daily practices, and confidence in maintaining halal integrity. Most participants became more alert in checking ingredients, using halal-certified products, and ensuring cleanliness in food preparation. However, the study also highlights challenges issues such as unclear labeling, difficulty in verifying imported items, and a lack of certified suppliers. Based on the findings, this research recommends conducting halal training at least twice a year, incorporating real-life kitchen scenarios, label-reading exercises, and audit simulations. These improvements aim to strengthen food handlers’ practical understanding of halal requirements and support Malaysia’s broader goal of becoming a global leader in the halal industry.